E-ESSENCE: electronic emotional and social support for Special Educational Needs (SEN) learners’ community in higher education / Roslinda Alias … [et al.] - Alias, Roslinda; Alias, Nor Aziah; Ibrahim, Abu Bakar; Jalaluddin, Jamizan; Mohd Rom, Kamarol Baharen (Research Innovation Business Unit, 2014)
E-ESSENCE or Electronic Emotional and Social Support for Special Educational Needs (SEN) Learners’ Community in Higher Education exemplify a component of the Model of Technology Supported Learning for SEN Learners at institutions of higher learning (IHL). The Model of Technology Supported Learning for SEN Learners was developed based on the needs and challenges faced by SEN in Malaysian IHL. Although these SEN learners receive support from their respective IHL, the support is not enough for them to sustain their life as IHL learners. Various barriers faced by SEN learners were identified in the research done by Roslinda Alias, Nor Aziah Alias and Abu Bakar Ibrahim (2014). One main barrier was lack of awareness and knowledge among the non-SEN learners and IHL staff on addressing the needs and challenges faced by SEN learners in their learning process and in their entire realm as IHL learners. Roslinda Alias et. al (2014) also found that SEN learners in Malaysian IHL felt inferior due to their conditions. This inadvertently impacted their academic performance. Thus, the Model of Technology Supported Learning for SEN Learners has been developed to address the needs and challenges faced by the SEN learners in Malaysian IHL. The model is based on two needs assessments conducted among the public and 66 SEN learners from eight Malaysian public IHL. During the needs assessments, challenges and needs of SEN learners were observed. Then, content analysis of the eight selected IHL websites was conducted as the foundation of the model prototype. The Model of Technology Supported Learning for SEN Learners was then validated by a heterogeneous group of 11 subject matter experts (SMEs) from overseas and local via the Delphi technique. Delphi technique as described by Dalkey (1967), is a “a set of procedures for eliciting and refining the opinions of a group of people” (p.1). The consensus among the SMEs was achieved at the Round Two of Delphi. This indicates that the Model of Technology Supported Learning for SEN Learners is feasible and accepted to be implemented in the Malaysian IHL. For this project, an e-group i.e. e-ESSENCE has been chosen to exemplify the Model of Technology Supported Learning for SEN Learners. The focus of this project was to provide emotional and social support for SEN learners’ community in IHL. Thus, two e-groups (e-ESSENCE) were created. A social media was selected as the platform to exemplify e-ESSENCE due to its renowned function in connecting people virtually in an effective and efficient way. Bugeja (2006) and Selwyn (200) also highlighted the vital functions of the selected social media in personal as well as social life of IHL learners. E-ESSENCE was found to have a great potential in supporting the emotional and social needs of the SEN learners in IHL. With the support from the Academia of Special Community Network, AIC, ICAN; Universiti Teknologi MARA (UiTM) was chosen to exemplify the e-ESSENCE due to its features of being the largest IHL with the largest SEN learners in Malaysia.